Reversible Myocarditis after Black Widow Spider Envenomation - Tarek Dendane; Khalid Abidi; Naoufel Madani; Asmae Benthami; Fatima-Zohra Gueddari; Redoune Abouqal; Amine-Ali Zeggwagh (Case Reports in Medicine)
Black widow spiders can cause variable clinical scenarios from local damage to very serious conditions including death. Acute myocardial damage is rarely observed and its prognostic significance is not known. We report a rare case of a 35-year-old man who developed an acute myocarditis with cardiogenic pulmonary edema requiring mechanical ventilation caused by black widow spider's envenomation. The patient was previously healthy. The clinical course was associated with systemic and cardiovascular complaints. His electrocardiogram revealed ST-segment elevation with T-wave amplitude. The plasma concentrations of cardiac enzymes were elevated. His first echocardiography showed hypokinesis of the left ventricle (left ventricle ejection fraction 48%). Magnetic resonance imaging showed also focal myocardial injury of the LV. There was progressive improvement in cardiac traces, biochemical and echocardiographical values (second left ventricle ejection fraction increased to 50%). Myocardial involvement after a spider bite is rare and can cause death. The exact mechanism of this myocarditis is unknown. We report a rare case of acute myocarditis with cardiogenic pulmonary edema requiring mechanical ventilation caused by black widow spider's envenomation. We objectively documented progressive clinical and electrical improvement.